The Combination of Small Group Discussion and ARCS (MODis-ARCS Strategy) to Improve Students’ Verbal Communication Skill And Learning Outcomes - Dewi, Ika Nurani; Safnowandi, S. (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
This study aimed at discovering the implementation of MODis-ARCS strategy to students’ verbal communication skill and learning outcomes. This study was a quasi-experimental using non- equivalent control group design. Purposive sampling was used to collect the data. There were 65 students of information technology education (control) and physics education (experimental) who used as the samples of study. The MODis-ARCS strategy was implemented on the experimental group, while small group discussion was used in the control group. Data collection techniques used test instrument that was in the form of essay items and non-test which was in the form of observation sheets of communication skill. Validity scores, Cronbach’s coefficient alpha, n-gain, independent sample t-test and paired t-test were used as the data analysis techniques. The results of study indicated that 1) n-gain of students’ learning outcomes and verbal communication skill for the control group was 0.12 and 0.07, in which it was categorized as low, while for the experimental group was 0.29 and 0.48 in the moderate category. 2) Both of groups had similar initial abilities, and there was a difference on the learning outcomes, as well as the verbal communication skill between the control and experimental classes, 3) There was an improvement on the students’ learning outcomes and verbal communication skill on the control and experimental groups, in which the significance value was ɑ=5%; however, the improvement of experimental group was greater than the control group. Therefore, it can be concluded that the MODis-ARCS strategy can improve the students’ verbal communication skill and learning outcomes.